Life Satisfaction and Age : Dealing with Underidentification in Age-Period-Cohort Models - de Ree, J.; Alessie, R. (2012)
Recent literature typically finds a U shaped relationship between life satisfaction and age. Age profiles, however, are not identified without forcing arbitrary restrictions on the cohort and/or time profiles. In this paper we report what can be identified about the relationship between life satisfaction and age without applying such restrictions. Also, we identify the restrictions needed to conclude that life satisfaction is U shaped in age. For the case of Germany, we find that the relationship between life satisfaction and age is indeed U shaped, but only under the untestable condition that the linear time trend is negative and that the linear trend across birth cohorts is practically flat.